Analisis Pengelolaan Dana Partai Terhadap Masa Depan Partai Politik: Sebuah Kajian Penguatan Party-ID Terhadap Partai Politik Baru 2019 - Moh. Arief Rakhman; Hatta Abdi Muhammad (Journal of Politics and Policy, 2019)
This article tries to look at the opportunities that new political parties in Indonesia have to provide political education related to the issue of political finance transparency as social capital in increasing participation to electoral support in society. The Law on Public Information Openness (UU KIP) and the Law on Political Parties have obliged political parties to manage their finances with the principles of transparency and accountability, but most have not yet revealed the reporting of political party financial reports that are publicly published. Focusing on the emergence of 4 (four) new political parties that participated in the 2019 election contestation, gave rise to opportunities to be able to attract voter sympathy in order to gain electoral potential by demonstrating internal financial management, bringing transparency through clear financial reports. With a descriptive qualitative approach it was found that the relationship between the identity of political parties and the management of political party funds towards 4 (four) new political parties was still weak. This phenomenon is a result of still being "blurred" and covered by issues of transparency and accountability of funding by new political parties.